2008
DOI: 10.1189/jlb.0108035
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression is down-regulated by angiotensin II and under hypertension in human neutrophils

Abstract: Angiotensin II (Ang II) is a peptide hormone able to elicit a strong production of reactive oxygen species by human neutrophils. In this work, we have addressed whether expression of heme oxygenase-1 (HO-1), an antioxidant enzyme, becomes altered in these cells upon Ang II treatment or under hypertension conditions. In neutrophils from healthy and hypertensive subjects, induction of HO-1 mRNA and protein expression with a parallel increase in enzyme activity took place upon treatment with 15-deoxy-Delta12,14-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…It was stated that MEL-and ALC-induced neuroprotective activity is mediated via the potentiation of other brain antioxidants (e.g., GST-P1, ascorbic acid, and other, yet unidentified, compounds) that, by altering the cell's redox state, they could attenuate the subsequent activation of NF-κB and AP-1. Indeed, the induction of HO-1 expression is a NO-dependent process [5], and the significant inhibition of NOS-1 and NOS-2 mRNA expression given by MEL and ALC may be inhibition of the gene expression of HO-1 and HO-2 as indicated in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…It was stated that MEL-and ALC-induced neuroprotective activity is mediated via the potentiation of other brain antioxidants (e.g., GST-P1, ascorbic acid, and other, yet unidentified, compounds) that, by altering the cell's redox state, they could attenuate the subsequent activation of NF-κB and AP-1. Indeed, the induction of HO-1 expression is a NO-dependent process [5], and the significant inhibition of NOS-1 and NOS-2 mRNA expression given by MEL and ALC may be inhibition of the gene expression of HO-1 and HO-2 as indicated in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Our group has previously shown that HO1 synthesis is induced by 15dPGJ 2 in neutrophils, and that HO1 expression (at the mRNA and protein levels) and activity are downregulated in both neutrophils from healthy subjects treated with Ang II and in untreated neutrophils from hypertensive patients (Alba et al 2008). As Ang II is able to induce both CN synthesis and activity in human neutrophils, we have examined in this work the possibility that the Ang II effect observed on HO1 might be mediated by CN.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we found that Ang II treatment before 15dPGJ 2 addition significantly prevented nuclear accumulation of Nrf2 (Alba et al 2008). We have now studied the possible participation of CN in NRF2 expression.…”
Section: Implication Of Cn In Oxidative Stress In Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations